The Constitutive Model of Rockfill Based on Property-Dependent Plastic Potential Theory for Geomaterials - Xuefeng Li; Ruijie Li; Junhui Zhang; Qi Wang (Advances in Civil Engineering)
To better control the strength and deformation of the roadbed, a constitutive model of rockfill was established based on property-dependent plastic potential theory for geomaterials. The effect of the particle gradation on the anisotropy was described in the model. According to the effect of the particle grading and crushing on the fractal dimension, the fractal theory and fabric tensor were introduced to establish the yield and failure criteria of the rockfill. By combining the property-dependent concepts of the materials and the results of the rockfill strength test, a critical state line considering the microstructure, fractal dimension, particle breakage, and stress state of the rockfill was established. The dilatancy equation was derived based on the novel potential theory and the hardening criterion affected by the critical state was established. A constitutive model of the rockfill in the general stress space was established under the framework of the novel potential theory. The 3D strength and its intensity change in the π plane were simulated through the drainage strength test results, which verified the description of the critical state under various stress paths. By simulating the stress-strain relationship, the validity and rationality of the model were verified.